2021
DOI: 10.1038/s41422-021-00473-1
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with influenza A virus enhances SARS-CoV-2 infectivity

Abstract: The upcoming flu season in the Northern Hemisphere merging with the current COVID-19 pandemic raises a potentially severe threat to public health. Through experimental coinfection with influenza A virus (IAV) and either pseudotyped or live SARS-CoV-2 virus, we found that IAV preinfection significantly promoted the infectivity of SARS-CoV-2 in a broad range of cell types. Remarkably, in vivo, increased SARS-CoV-2 viral load and more severe lung damage were observed in mice coinfected with IAV. Moreover, such en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
211
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(229 citation statements)
references
References 33 publications
12
211
2
4
Order By: Relevance
“…Due to the seasonality of influenza outbreaks and the continuous prevalence of COVID-19, influenza could circulate in parallel with COVID-19, which largely increases the potential risk of co-infection. Though little is known about the epidemiology and clinical outcomes of co-infection, extant literature has found that the co-infection with influenza A virus enhances the infectivity of COVID-19 in a broad range of cell types [3], whereas co-infected patients seem to present similar clinical symptoms and radiological images compared with patients infected with COVID-19 alone [4,5]. In the context of the COVID-19 pandemic, the dual infection of influenza and COVID-19 could bring extra burden to health care services by utilizing limited medical resources, increasing the difficulty of treatment and the uncertainty of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the seasonality of influenza outbreaks and the continuous prevalence of COVID-19, influenza could circulate in parallel with COVID-19, which largely increases the potential risk of co-infection. Though little is known about the epidemiology and clinical outcomes of co-infection, extant literature has found that the co-infection with influenza A virus enhances the infectivity of COVID-19 in a broad range of cell types [3], whereas co-infected patients seem to present similar clinical symptoms and radiological images compared with patients infected with COVID-19 alone [4,5]. In the context of the COVID-19 pandemic, the dual infection of influenza and COVID-19 could bring extra burden to health care services by utilizing limited medical resources, increasing the difficulty of treatment and the uncertainty of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we and others have shown that IAV pre-infection of hACE2 mice results in more severe SARS-CoV-2 associated pulmonary changes and higher amounts of infectious virus at or 7 days post SARS-CoV-2 infection (Bai et al, 2021;Clark et al, 2021). Interestingly though, viral loads in the brain were not found to be increased (Bai et al, 2021), although we observed higher frequency and more widespread brain infection after the lower SARS-CoV-2 dose in animals that were infected with IAV. Also, the inflammatory response was slightly more intense in these animals.…”
Section: Resultsmentioning
confidence: 73%
“…Also, the inflammatory response was slightly more intense in these animals. It is currently unclear which direct impact IAV infection has for the subsequent SARS-CoV-2 challenge, but more efficient virus entry could be an option, since IAV infection was shown to upregulate ACE2 expression in vitro (Bai et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report in Cell Research, Bai et al 2 found that cells, whether susceptible or not to SARS-CoV-2, became significantly more sensitive to SARS-CoV-2 after infection with IAV (A/WSN/ 1933(H1N1)). In addition, coinfection of IAV and SARS-CoV-2 in mice resulted in increased viral load of SARS-CoV-2 and more severe lung damage.…”
mentioning
confidence: 99%
“…Bai et al 2 also found that other respiratory viruses, such as human respiratory syncytial virus (HRSV), human parainfluenzavirus (HPIV), and human rhinovirus 3 (HRV3), did not appear to promote SARS-CoV-2 infection, thus providing a tentative diagnostic basis for pathogen co-monitoring, alongside SARS-CoV-2, in the clinic. This study also reported that the auxo-action of IAV to SARS-CoV-2 infection may come from the elevated ACE2 expression induced by IAV (Fig.…”
mentioning
confidence: 99%